Elevated mRNA expression levels of inflammation-related genes in triple-negative breast cancer: A pilot study from North East India - Rizwana Sultana; Syed Javed Salman Chisty (Annals of Oncology Research and Therapy, 2021)
BACKGROUND: The prevalence of Triple-Negative breast cancer (TNBC) accounts for a large percentage of breast cancer cases in India. TNBC is associated with poor prognosis, higher mortality rate, ill-defined molecular etiology, and hence limited therapeutic interventions. AIM: The aim of this study is to evaluate the association of certain inflammatory markers with TNBC pathogenesis. MATERIALS AND METHODS: Prospectively collected resected breast cancer tissue samples along with adjacent normal control (n = 100) were prospectively collected in RNA Later. Differential mRNA expression analysis of inflammatory-related genes namely; inducible nitric oxide synthase (iNOS), endothelial nitric oxide synthase (eNOS), cyclooxygenase-2 (COX2), and Nuclear Factor Kappa B (NFκB) and were evaluated in non-TNBC and TNBC tissues samples along with adjacent normal control tissue samples with the help of mRNA specific primers using reverse transcription-polymerase chain reaction. Statistical analysis was performed using SPSSv13.0 software. RESULTS: A total of 60 non-TNBC and 40 TNBC tissue samples along with adjacent normal control were included for the study with informed consent and clinical details. The mean age of the TNBC patients was 39 ± 9 years, All the breast cancer cases were clinically staged as Infiltrating Duct Carcinoma (non-TNBC-invasive ductal carcinoma [IDC] II [n = 29 cases], non-TNBC-IDC III [n = 31 cases], TNBC-IDCII [n = 22 cases], TNBC-IDC III [n = 18 cases]). The results showed an upregulation of all the markers in TNBC cases compared to non-TNBC vis-avis non-neoplastic adjacent control area. Second, significant changes in iNOS mRNA expression were found to be associated with severity of TNBC cases (P = 0.020), while the expression of constitutively expressed eNOS was comparative between IDC-II and IDC-III stages of TNBC. CONCLUSIONS: The present study indicates that the mRNA-based differential expression results showed an upregulation of all the markers (iNOS, eNOS, COX2, and NFκB) in TNBC cases compared to non-TNBC cases vis-a-vis non-neoplastic adjacent control area. Significant changes in iNOS mRNA expression were found to be associated with severity of TNBC cases (P = 0.020), depicting the role of iNOS-induced inflammation in the pathogenesis of TNBC.